The Extensive Parameters as a Tool to Monitoring the Volcanic Activity: The Case Study of Vulcano Island (Italy) - Inguaggiato, Salvatore; Vita, Fabio; Diliberto, Iole Serena; Mazot, Agnes; Calderone, Lorenzo; Mastrolia, Andrea; Corrao, Marco (Remote sensing (Basel, Switzerland), 2022)
On Vulcano Island (Italy), many geochemical crises have occurred during the last 130 years of solfataric activity. The main crises occurred in 1978–1980, 1988–1991, 1996, 2004–2007, 2009–2010 and the ongoing 2021 anomalous degassing activity. These crises have been characterized by early signals of resuming degassing activity, measurable by the increase of volatiles and energy output emitted from the summit areas of the active cone, and particularly by increases of gas/water ratios in the fumarolic area at the summit. In any case, a direct rather than linear correspondence has been observed among the observed increase in the fluid output, seismic release and ground deformation, and is still a subject of study. We present here the results obtained by the long-term monitoring (over 13 years of observations) of three extensive parameters: the SO2 flux monitored in the volcanic plume, the soil CO2 flux and the local heat flux, monitored in the mild thermal anomaly located to the east of the high-temperature fumarole. The time variations of these parameters showed cyclicity in the volcanic degassing and a general increase in the trend in the last period. In particular, we focused on the changes in the mass and energy output registered in the period of June–December 2021, to offer in near-real-time the first evaluation of the level and duration of the actual exhalative crisis affecting Vulcano Island. In this last event, a clear change in degassing style was recorded for the volatiles emitted by the magma. For example, the flux of diffused CO2 from the soils reached the maximum never-before-recorded value of 34,000 g m−2 d−1 and the flux of SO2 of the plume emitted by the fumarolic field on the summit crater area reached values higher than 200 t d−1. The interpretation of the behavior of this volcanic system, resulting from the detailed analyses of these continuous monitoring data, will complete the framework of observations and help in defining and possibly forecasting the next evolution of the actual exhaling crisis.